A correlation study between serum direct bilirubin and lipid in type 2 diabetic patients - Wang, Ru; Yang, Guoqing; Lyu, Zhaohui; Dou, Jingtao; Gu, Weijun; Zang, Li; Jin, Nan; Du, Jin; Ouyang, Jinzhi; Guo, Qinghua; Wang, Xianling; Yang, Lijuan; et al. (Chung-hua nei kʿo tsa chih, 2014)
To investigate the association between DBil with normal range and serum lipid in type 2 diabetic patients. A total of 979 subjects with type 2 diabetes admitted to the Department of Endocrinology of Chinese PLA General Hospital from June 2012 to June 2013 were included for the study. Serum DBil, TC, TG, HDL-C and LDL-C levels were collected for the analyses. Subjects were divided into four groups based on the DBil levels: Q1 group (<2.2 µmol/L), Q2 group (2.2-< 2.9 µmol/L), Q3 group (2.9-< 3.9 µmol/L) and Q4 group ( ≥ 3.9 µmol/L) . (1) TC, TG, LDL-C levels were significantly lower in Q4 group than those in the other three Q groups after adjustment of age, gender, duration of diabetes, BMI, smoking, drinking, glycosylated hemoglobin A1c (HbA1c) , fasting plasma glucose (FPG), medication, ALT, AST and fatty liver. No difference could be viewed in HDL-C level between each group (P = 0.65). (2) Pearson correlation analyses showed that DBil was inversely correlated with TC (r = -0.33, P < 0.01), TG (r = -0.23, P <